UMA ANÁLISE DA RELAÇÃO ENTRE VARIÁVEIS MACROECONÔMICAS E O COMPORTAMENTO DAS AÇÕES DE MAIOR LIQUIDEZ DO ÍNDICE IBOVESPA - ANDRADE, DANIELA DE (2015)
The most liquid shares of the IBOVESPA index, reflect the behavior of stocks in general, and the relationship of macroeconomic variables in their behavior and are among the most actively traded securities in the Brazilian capital market. Thus, one can understand that there are consequences of factors that impact the most liquid companies that define the behavior of macroeconomic variables and the reverse is also true, fluctuations in macroeconomic factors also affect the most liquid stocks, as IPCA, GDP Selic and exchange rates. The study proposes an analysis of the relationship between macroeconomic variables and the behavior of most liquid shares of the IBOVESPA bovespa index, corroborating studies that seek to understand the influence of macroeconomic factors on the stock price and empirically contributing to the formation of investment portfolios. The work covered the period from 2008 to 2014. The results concluded that the formation of portfolios in order to protect the invested capital, must contain assets with negative correlation in relation to variables, which makes possible the composition of a reduced risk with portfolio.